049 Characterising behaviour in behavioural variant frontotemporal dementia and semantic dementia. Issue 12 (14th November 2019) - Heartshorne, Rosie; Jones, Matthew; Kobylecki, Christopher; Snowden, Julie S; Thompson, Jennifer C
Abstract : Frontotemporal dementia (bvFTD) and semantic dementia (SD) are canonical syndromes associated with frontotemporal lobar degeneration. Change in behaviour is the cardinal symptom in bvFTD but is also observed in SD. We aimed to identify behaviours specific to each of these conditions and explore correlations between behaviours and regional atrophy. We performed retrospective analysis of clinical data in 84 patients with bvFTD and SD presenting to a tertiary cognitive neurology clinic. Behaviours were rated on an internally developed proforma, and a visual rating scale was used to grade atrophy on MR scan. A chi-squared test was used for comparative analysis of behaviours and Spearman's Rank Correlation Coefficient for imaging and behaviour. Blunted affect, poor self-care, and loss-of-empathy were highly specific to bvFTD (P<0.001). Loss-of-empathy correlated with orbitofrontal and dorsolateral frontal cortical atrophy (<0.05). Food fads (P=0.003) and number games (P=0.001) were highly specific for SD. Food fads were associated with left anterior fusiform atrophy (P=0.004), and number games with posterior temporal atrophy (P<0.05). This study identified certain behavioural features specific for each syndrome, which has implications for accurate diagnosis. Behaviours specific to bvFTD were associated with regional frontal atrophy, whereas those seen in SD correlated more strongly with temporal atrophy.